Causes of Accidents Involving Scaffolding at Construction Sites - Abas, Nor Haslinda; Noridan, Muhammad Ridhwan; Rahmat, Muhamad Hanafi; Abas, Nor Ain; Ibrahim, Nur Qamarina (Journal of Technology Management and Business, 2020)
According to the fatal accident cases reported by the Department of Occupational Safety and Health (DOSH), accidents related to the used of scaffolding was one of the significant types of the fatal accident at the construction sites. Scaffolding was usually used when it was involved with working at height activity. This paper presents the analysis of the significant causes of accidents involving scaffolding at construction sites based on the perceptions of safety personnel. It was involved in distributing the questionnaire surveys to safety personnel who were working at the construction sites in Johor. The data were analyzed by using the Average Mean Index and Relative Importance Index (RII). From the study, the main causes of scaffolding accidents were ignoring safety rules, improper inspections, and improper foundation/stability. It is hoped that the findings of this study will be taken as a reference to construction employers in understanding the factors that contribute to scaffolding-related accidents.